Alternative Preservation Networks: Profiling the Old Time Radio Researchers Group. Issue 1 (2nd April 2020) - Jones, Sammy; Kornman, Paul
Abstract: While work on radio preservation in archival scholarship has focused predominantly on projects and strategies in formal library and archiving institutions, private collectors have also developed longstanding preservation networks and protocols that operate outside of professional LIS institutions. The Old Time Radio Researchers is an all-volunteer, nonprofit organization dedicated to the preservation and study of the "Golden Age of Radio" from 1930 – 1950. Founded in 2003, the OTTR Group has located recordings of over 60, 000 extant network radio broadcast to date, along with related print, graphical, and Internet resources, and makes digitized copies of these materials freely available to the public through its online archive at http://otrr.org . In this interview, Sammy Jones, who compiles metadata on holdings of private collectors as a Program Network Director for the Radio Preservation Task Force of the Library of Congress's National Recording Preservation Board, talks with Paul Kornman, Director of the Old Time Radio Researchers, about OTRR's collecting and metadata practices.